CFO tenure, CFO board membership and accounting conservatism. Issue 3 (December 2019) - Muttakin, Mohammad Badrul; Khan, Arifur; Tanewski, George
Abstract: We examine the influence of chief financial officer (CFO) tenure and CFO board membership on accounting conservatism among Australian listed companies. The study uses market-based (i.e., timeliness of earnings to news) and accounting-based (i.e., accrual-based loss recognition) measures of conservative accounting. The results show that while longer CFO tenure and CFO board membership increases accounting conservativism, this is not the case when CFOs become entrenched through long board-membership tenure. This entrenchment appears to lead to the use of aggressive accounting practices. Overall, the results indicate that CFO tenure and CFO board membership improve financial-reporting quality by increasing accounting conservatism in organizations, providing evidence of the importance of recognizing these two governance characteristics in policymaking and in regulation.